Molnupiravir: A Prodrug of the Ribonucleoside β‐D‐N4‐Hydroxycytidine Triphosphate Inhibits the Propagation of Nervous Necrosis Virus in Grouper Brain Cells - Chen‐Kung Chi; Vertika Bajpai; Chen‐Hung Li; Hsin‐Yi Tsai; Chien‐Wen Chen; Chao‐An Cheng; Hsia‐Wei Liu; Chi‐Yao Chang (Journal of Fish Diseases, 2026)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis, otherwise known as viral encephalopathy and retinopathy in larval and juvenile marine fish worldwide. The pandemic outbreaks have caused nearly 100% mortality in hatcheries, leading to significant economic losses in the aquaculture industry. Since NNV attacks the insufficient immune competence fish at early developmental stages, there is an urgent need for effective antiviral drugs. Several nucleoside analogues, including Molnupiravir, have been developed to target viral RNA‐dependent RNA polymerase (RdRp). This study examines the antiviral activity of Molnupiravir against NNV isolated from giant grouper (GG), Epinephelus lanceolatus (Bloch), using grouper brain (GB) cells as an infection model. The inhibition concentration for 50% of maximal effect (EC 50 ) of Molnupiravir on GGNNV propagation in GB cells was determined as 1.87 μM. Surprisingly, the titre of GGNNV reduced 50,000 at 100 μM of Molnupiravir treatment at 4‐day post‐infection, whereas treatment with 200 μM of Molnupiravir resulted in a 10 5 reduction in viral titre. The inhibition of viral replication and translation was further examined using RNA‐fluorescence in situ hybridization (FISH) and immunocytochemistry detection, respectively. Moreover, administration of 100 μM Molnupiravir at early time 0 hpi resulted in a dramatic decrease in viral load, reducing cell‐associated virus by approximately 4000‐fold and released virus by 6000‐fold. Finally, the molecular docking simulation model supports the interaction between NHC‐TP and GGNNV RdRp for the successful therapeutics. These results demonstrated that Molnupiravir is a very effective therapeutic drug for controlling viral nervous necrosis caused by NNV infection.

Statistical optimization of biochar production via high-temperature carbonization through Taguchi and principal component analysis approaches - Jamin Jamir Escalante; Wei-Hsin Chen; Chien-Yuan Su; Po-Han Li; Kun-Yi Andrew Lin; Kanit Manatura (Fuel, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Research note: assessing human preferences for natural landscapes—an analysis of ChatGPT-4 and LLaVA models - Yu-Hsin Tung; Zhe-Rui Yang; Meng-Wei Shen; Chun-Yen Chang; Chien-Chung Chen; Li-Chih Ho (Landscape and Urban Planning, 2025)

Prediction construction for biomass and high-density polyethylene co-gasification via statistical method and machine learning - Jamin Jamir Escalante; Wei-Hsin Chen; Wan Mohd Ashri Wan Daud; Chien-Yuan Su; Po-Han Li (Fuel, 2025)

Catalytic co-gasification optimization of biomass and polyethylene wastes in oxygen-rich environments - Wei-Hsin Chen; Jamin Escalante; Liu Li Xuan; Ria Aniza; Chien-Yuan Su; Po-Han Li (Fuel, 2025)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Determination of 16 ultraviolet–absorbing compounds in marine invertebrates by using LC-USI-MS/MS coupled with QuEChERS - Yu-Fang Huang; Yan-Jun Liu; Kai-Chien Yang; Zi-Ying Li; Chia-Hsin Liu; Hsin-Chang Chen (Food Chemistry, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Climate risk analysis of low-altitude tea gardens in central Taiwan using a Bayesian network - Yung-Chieh Wang; Chien-Teh Chen; Rui-Yu Li; Yu-Hsin Lu; Li-Chi Chiang (Environmental Monitoring and Assessment, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

Appropriate management practices help enhance odonate species richness of small ponds in peri-urban landscapes - Wen-Chieh Chien; Mei-Hui Li; Hsin-Ju Li (Urban Ecosystems, 2019)

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation - Edy Kornelius; Hsin-Hua Li; Chiung-Huei Peng; Hui-Wen Hsiao; Yi-Sun Yang; Chien-Ning Huang; Chih-Li Lin (Metabolic Brain Disease, 2017)

Impact of absorbing aerosol deposition on snow albedo reduction over the southern Tibetan plateau based on satellite observations - Wei-Liang Lee; K. N. Liou; Cenlin He; Hsin-Chien Liang; Tai-Chi Wang; Qinbin Li; Zhenxin Liu; Qing Yue (Theoretical and Applied Climatology, 2017)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Concurrent use of antiplatelets, anticoagulants, or digoxin with Chinese medications: a population-based cohort study - Hsin-Hui Tsai; Hsiang-Wen Lin; Chun-Ru Chien; Tsai-Chung Li (European Journal of Clinical Pharmacology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Absorption Kinetics of Nitrogen Oxides using Sodium Chlorite Solutions in Twin Spray Columns - Tsung Wen Chien; Hsin Chu; Yarn-CHI Li (Water, Air, & Soil Pollution, 2005)

Dating the Monocot?Dicot Divergence and the Origin of Core Eudicots Using Whole Chloroplast Genomes - Chien-Chang Chang; Hsin-Liang Chen; Wen-Hsiung Li; Shu-Miaw Chaw (Journal of Molecular Evolution, 2004)